Optimizing SEO (Search Engine Optimizing) Strategy to Increase Visibility and Achievement of Marketing Goals - Jusuf, Dewi Indriani (International Publisher, 2023)
This research aims to identify and optimize SEO (Search Engine Optimization) strategies to increase visibility and achieve marketing goals. With the emergence of the internet as a major platform for various business activities, it is important for companies to highlight their presence among competitors by maximizing effective SEO strategies. This research uses a qualitative approach with descriptive methods. The results of this research show that implementing an effective SEO strategy can significantly increase the visibility and organic traffic of a website, which in turn can contribute to increased brand awareness, increased visitor numbers, and the potential for increased sales conversions. By focusing on ethical practices and using methods that comply with search engine guidelines, companies can harness the potential of SEO to strengthen their position in an increasingly competitive digital marketplace, create customer trust, and ensure long-term success in their marketing efforts.